Ultrasound cavitation intensified amine functionalization: A feasible strategy for enhancing CO2 capture capacity of biochar. (1st August 2018) - Chatterjee, Riya; Sajjadi, Baharak; Mattern, Daniell L.; Chen, Wei-Yin; Zubatiuk, Tetiana; Leszczynska, Danuta; Leszczynski, Jerzy; Egiebor, Nosa O.; Hammer, Nathan
Graphical abstract: Highlights: Ultrasound irradiation was applied for physical treatment of biochar at room temperature. The sono-treated biochar was functionalized with tetraethylenepentamine (TEPA). The modified biochar demonstrated a great potential for CO2 capture. Abstract: This paper describes a two-stage biochar activation process for CO2 capture, which includes acoustic treatment and amination. Contrarily to traditional carbon activation at temperatures above 700 °C, both stages of the current process are conducted at or near room temperature. It is known that CO2 can be fixed on the edge carbons of polycyclic aromatics hydrocarbons (PAHs) through thermal and reductive photo-carboxylation. Our previous work on biochar suggested that carbon of CO2 could be chemically fixed on biochar through acoustic or photochemical treatment of biochar in water/CO2 systems under ambient conditions. Separately, the graphene oxide (GO) literature reveals that carboxylic acids, epoxy and hydroxyl groups on biochar surface often serve as the active sites for converting GO to a new family of chemicals; amines are commonly grafted on these groups in the functionalization. Biochar has graphite and graphitic oxide clusters that consist of the oxygen functional groups mentioned above. These oxygen functionalities can be utilized for CO2 adsorption when functionalized with amine. Thus, the present study focuses on maximizing the CO2 capture capacity by manipulating the physicochemical structure of a pinewood-derived biochar. In this two-stage process, 30 s sonication at ambient temperature was applied to physically activate biochar prior to functionalization. Low-frequency ultrasound irradiation exfoliates and breaks apart the irregular graphitic layers of biochar, and creates new/opens the blocked microspores, thus enhancing the biochar's porosity and permeability that are the keys in functionalization and subsequent CO2 capture. The sono-modified biochar was then functionalized with tetraethylenepentamine (TEPA) in the presence of two activating agents. The changes in surface characteristics, functional groups, graphene-like structure, and functionalization using activating agents were examined in detail and the capacity of the final products in CO2 removal was tested. The experimental results revealed that CO2 capture capacity, from a flow containing 10 and 15 vol% CO2, was almost 7 and 9 times higher, respectively, for ultrasound-treated amine-activated biochar, compared to raw biochar. The optimum capacity was 2.79 mmol/g at 70 °C and 0.15 atm CO2 partial pressure. Cyclic adsorption and desorption tests revealed that the CO2 capture capacity decreased 44% after 15 cycles.